The Effect of Profit Sharing Financing and Trading on Financial Performance: FDR as a Moderating Variable at Bank Aceh Syariah - Afrida, Riga; Hastuti, Cut Sri Firman; Rahmazaniati, Linda (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to assess how profit-sharing financing and sale-based financing affect financial performance (Return on Assets/ROA) and to re-examine the role of the Financing to Deposit Ratio (FDR) as a moderating variable in the relationship between profit-sharing and sale-based financing and financial performance (ROA). The population of this study is based on the monthly financial statements of Bank Aceh Syariah published from January 2020 to December 2024, totaling 60 reports. The sample selection in this study was conducted using the total sampling method. Data analysis was carried out using moderated regression analysis (MRA). The data were processed using SPSS version 26, yielding results that indicate that profit-sharing financing partially has no effect on financial performance (ROA), while sale-based financing partially has a significant effect on financial performance (ROA). The Financing to Deposit Ratio (FDR) is unable to moderate the relationship between profit-sharing and sale-based financing and financial performance (ROA). Simultaneously, profit-sharing and sale-based financing are found to influence financial performance (ROA) at Bank Aceh Syariah.